2023
DOI: 10.1001/jamanetworkopen.2023.12443
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Genotype-Specific Tricyclic Antidepressant Dosing in Patients With Major Depressive Disorder

Abstract: ImportanceEvidence of the clinical benefit of pharmacogenetics-informed treatment (PIT) with antidepressants is still limited. Especially for tricyclic antidepressants (TCAs), pharmacogenetics may be of interest because therapeutic plasma concentrations are well defined, identification of optimal dosing can be time consuming, and treatment is frequently accompanied by adverse effects.ObjectiveTo determine whether PIT results in faster attainment of therapeutic TCA plasma concentrations compared with usual trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…A 12-week, double-blind, parallel, multicenter randomized controlled trial by Pérez et al in 316 adult patients with major depressive disorder (MDD) evaluated the effectiveness of preemptive PGx testing-guided therapy over treatment as usual (TAU) and revealed that, in addition to significant improvement in treatment response, the burden of side effects was significantly reduced at 12 weeks in the PGx-guided treatment group [ 36 ]. In another multicentre randomized clinical trial in the Netherlands, Vos, Cornelis et al compared preemptive PGx informed treatment (PIT) with usual treatment among 111 patients with depressive disorders and reported that patients in the PIT group experienced fewer severe adverse effects than patients in the usual treatment group with faster attainment of therapeutic plasma concentrations [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…A 12-week, double-blind, parallel, multicenter randomized controlled trial by Pérez et al in 316 adult patients with major depressive disorder (MDD) evaluated the effectiveness of preemptive PGx testing-guided therapy over treatment as usual (TAU) and revealed that, in addition to significant improvement in treatment response, the burden of side effects was significantly reduced at 12 weeks in the PGx-guided treatment group [ 36 ]. In another multicentre randomized clinical trial in the Netherlands, Vos, Cornelis et al compared preemptive PGx informed treatment (PIT) with usual treatment among 111 patients with depressive disorders and reported that patients in the PIT group experienced fewer severe adverse effects than patients in the usual treatment group with faster attainment of therapeutic plasma concentrations [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unclear whether similar results can be achieved for other AD groups with less clear concentration-effect/side effect relationships. Furthermore, no significant reduction was seen in depressive symptoms [ 52 ]. With regard to the latter, a meta-analysis of five RCTs examining the effect of PGx-guided therapy on remission of depressive symptoms, showed that PGx-guided therapy with ADs had a positive effect on the likelihood of achieving remission in depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of pharmacogenetic studies have indicated that genetic testing prior to treatment may be useful either for setting the individual dose or for making the decision to use a particular drug [ 17 , 32 , 33 ] as well as for reducing clinically relevant ARDs by pre-emptive pharmacogenetic testing [ 34 , 35 ]. The era of very successful blockbuster drugs, the profitable ‘one-size-fits-all drugs’, is clearly declining [ 31 , 36 ].…”
Section: Discussionmentioning
confidence: 99%